147 Presynchronization and delayed fixed-time artificial insemination increases pregnancy rates with sex-sorted semen in replacement beef heifers. (30th November 2020) - Oosthuizen, Nicky; Fontes, Pedro; Filho, Ramiro; Dahlen, Carl R; Grieger, David M; Hall, John B; Lake, Scott; Looney, Charles; Mercadante, Vitor R G; Neville, Bryan W; Perry, George; Powell, Jeremy G; et al.
Abstract: To determine effects of presynchronization and delayed fixed-time artificial insemination (TAI) on pregnancy rates to TAI (PR/AI) with sex-sorted semen, 2, 855 Bos taurus beef heifers were enrolled in a completely randomized design. Within location, heifers were randomly assigned to one of eight treatments: 1 and 2), heifers were exposed to the 7-d CO-Synch+CIDR protocol wherein they received gonadotropin-releasing hormone (GnRH) and a CIDR insert on d 0, prostaglandin F2α (PGF) upon CIDR removal on d 7, and were TAI 54 ± 2 h later with conventional (CTRL54-CNV; n = 359) or sex-sorted semen (CTRL54-SEX; n = 356); 3 and 4), same as CTRL54 but were TAI at 72 ± 2 h with conventional (CTRL72-CNV; n = 366) or sex-sorted semen (CTRL72-SEX; n = 360); 5 and 6), same as CTRL54 but also received PGF 7 d prior to initial injection of GnRH (d -7) and were TAI with conventional (PRE54-CNV; n = 355) or sex-sorted semen (PRE54-SEX; n = 353); 7 and 8), same as PRE54 but had TAI delayed to 72 ± 2 h and were inseminated with conventional (PRE72-CNV; n = 351) or sex-sorted semen (PRE72-SEX; n = 355). All heifers received estrus detection patches on d 7, which were evaluated for activation at TAI. Ultrasonography was performed 30–45 d after TAI to determine PR/AI. Estrus expression was greater (P < 0.01) in the CTRL72 heifers compared to CTRL54, PRE54, and PRE72 heifers (73.0 vs 55.4, 43.4, and 65.7%, respectively). Moreover, estrus expression was greater (P < 0.01) in PRE72 heifers compared to CTRL54 and PRE54 heifers. Within treatment pairs, PR/AI were greater (P ≤0.04) when conventional semen was utilized compared to sex-sorted semen. Furthermore, PR/AI were greater (P = 0.02) in PRE72-SEX heifers than CTRL54-SEX heifers (45.8 vs. 37.5%). No difference (P = 0.20) was determined in PR/AI between CTRL54-CNV and PRE72-SEX heifers (50.5 vs. 45.8%). In conclusion, presynchronization in combination with delayed TAI increased estrus expression and PR/AI with sex-sorted semen in replacement beef heifers.